Culture, History, and the Reception of Tennessee Williams in China - Qi, Shouhua (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book is the first comprehensive study of the reception of Tennessee Williams in China, from rejection and/or misgivings to cautious curiosity and to full-throated acceptance, in the context of profound changes in China's socioeconomic and cultural life and mores since the end of the Cultural Revolution. It fills a conspicuous gap in scholarship in the reception of one of the greatest American playwrights and joins book-length studies of Chinese reception of Shakespeare, Ibsen, O'Neill, Brecht, and other important Western playwrights whose works have been eagerly embraced and appropriated and have had catalytic impact on modern Chinese cultural life.
1. Introduction -- 2. Speaking the Unspoken and the Unspeakable: Translating Tennessee Williams -- 3. From Cautious Curiosity to Deep Dive: Interpreting Tennessee Williams -- 4. Becoming Blanche Dubois: Adapting Tennessee Williams for the Chinese Stage -- 5. Conclusion.
Keywords: Oriental literature; Comparative literature; Theater; Literature, Modern-20th century; America-Literatures.; Adaptation (Literary, artistic, etc.).; Asian Literature; Comparative Literature; Global and International Theatre and Performance; Twentieth-Century Literature; North American Literature; Adaptation Studies